Dravet syndrome: New potential genetic modifiers, imaging abnormalities, and ictal findings. Issue 9 (28th June 2013) - Gaily, Eija; Anttonen, Anna‐Kaisa; Valanne, Leena; Liukkonen, Elina; Träskelin, Ann‐Liz; Polvi, Anne; Lommi, Markus; Muona, Mikko; Eriksson, Kai; Lehesjoki, Anna‐Elina
Summary Purpose Dravet syndrome is an autosomal dominant epileptic encephalopathy of childhood, which is caused mainly by SCN1A and PCHD19 mutations. Although Dravet syndrome is well recognized, the causes of acute encephalopathy are still elusive, and reported data on ictal electroencephalography (EEG) and structural brain abnormalities are scarce. Methods We studied 30 children who fulfilled the clinical criteria for Dravet syndrome. All patients were screened for SCN1A mutations and 25 for POLG mutations with bidirectional sequencing. Clinical data, including etiologic studies done as part of the clinical workup, were collected from hospital charts. Ictal video‐EEG recordings and magnetic resonance (MR) images were reanalyzed by the authors. Key Findings SCN1A mutations were found in 25 patients (83%). Two SCN1A mutation–negative patients had chromosomal translocations involving chromosomes 9 and X, and one had a mutation in PCDH19. Prolonged seizures were associated with acute encephalopathy in three SCN1A mutation–positive patients. One showed evidence of a significant hypoxic–ischemic event during status epilepticus. The other two demonstrated new persistent neurologic deficits postictally; they both carried heterozygous POLG variants (p.Trp748Ser or p.Gly517Val). Hippocampal sclerosis or loss of gray–white matter definition in the temporal lobe was observed in 7 of 18 patients who had MRI after age 3 years (39%). Motor seizures were recorded on video‐EEG for 15 patients, of whom 12 were younger than 6 years at recording; 11 patients (73%) showed posterior onsets. Significance Our data imply that a heterozygous X;9 translocation and rare POLG variants may modify the clinical features of Dravet syndrome. The latter may increase susceptibility for acute encephalopathy. Temporal lobe abnormalities are common in patients imaged after 3 years of age. Focal seizures seem to localize predominantly in the posterior regions in young children with Dravet syndrome.